Condition-dependent female remating resistance generates sexual selection on male size in a ladybird beetle - Perry, J; Sharpe, D; Rowe, L (2009)
Behavioural resistance to remating by females is common, but the causes and consequences of resistance are rarely explained. Prominent hypotheses include resistance as a means of avoiding costly and superfluous mating, or as a means of biasing mating towards high-quality males. In species in which males produce nutritious nuptial gifts, females may further modulate resistance according to their need for nutrition. We investigated these hypotheses in the ladybeetle Adalia bipunctata, in which females frequently display vigorous resistance before copulation and ingest a spermatophore after copulation. In two experiments, we manipulated female nutritional state, depriving or satiating females for a short (16 h) or long (96 h) interval before a remating trial. We found that food-deprived females resisted mating more frequently and for longer periods than satiated females and consequently remated less frequently. This condition dependence of resistance supports the hypothesis that resistance functions to reduce superfluous and costly mating. Our finding that food-deprived females were more resistant suggests that mating imposes energetic costs, and that nuptial feeding does not offset these costs. In a third experiment, we investigated whether the extent of resistance depended on male size or whether resistance itself biased mating towards large males. The extent of female resistance was independent of male size, but resistance itself resulted in a mating bias towards large males. In summary, our results support the hypotheses that females resist mating simply because it is costly and superfluous, and that a side effect of resistance is sexual selection for large male size. © 2009 The Association for the Study of Animal Behaviour.